Hip fractures in people with idiopathic Parkinson's disease: Incidence and outcomes. Issue 3 (6th February 2013) - Walker, Richard W.; Chaplin, Andrew; Hancock, Rebecca L.; Rutherford, Rachel; Gray, William K.
ABSTRACT The incidence of hip fracture and outcomes from hip surgery for people with Parkinson's disease (PD) are thought to be poorer than for people without PD. The aim of this audit of a prospective hip‐fracture database was to establish the incidence of, and outcomes from, hip fracture in people with and without PD living in North East England. The number of people with PD living in the study area was estimated using data from two previous prevalence studies in the same geographical area. Using data collected prospectively for the National Hip Fracture Database for Northumbria Healthcare National Health Service Foundation Trust in the UK, the annual incidence of hip fracture in people with and without PD was calculated. Type of fracture, time to surgery, time to discharge, and 30‐day outcomes from surgery were compared. Annual incidence of hip fracture was significantly higher in people with PD across all age bands. In those 60 years of age and over, it was 2, 171 (95% confidence interval [CI]: 2, 082–2, 264) per 100, 000 in people with PD and 551 (95% CI: 506–598) in people without PD. The experience of PD and non‐PD patients within hospital was remarkably similar. However, PD patients had poorer mobility before hip fracture, took longer to be discharged to the community, and were less mobile postsurgery. Specific guidelines for managing people with PD who sustain a hip fracture may help to improve awareness of the potential complications of the condition and improve outcomes. © 2012 Movement Disorder Society